The Efficacy of Green Grapefruit (Vitis Vinifera L) Extracts on Reducing Blood Glucose in a Diabetic Rat Model - Habibah, Nur; Rofi'ah, Lisa Khofidatur; Bekti, Heri Setiyo; Dewi, Ni Nyoman Astika; Wilankrisna, Luh Ade; Posmaningsih, Dewa Ayu Agustini (Medical Laboratory Technology Journal, 2024)
Diabetes mellitus (DM) is a chronic disease in which the pancreas cannot produce enough insulin hormone or when the body cannot use the insulin hormones properly. Green grapes contain flavonoids, anthocyanins, tannins, phenolic acids, and resveratrol and are high in antioxidants that are beneficial in lowering blood glucose levels. This study aims to determine the effectiveness of green grapefruit (Vitis vinifera L) extract in reducing blood glucose levels in a diabetic rat model. This research is a true experiment with a post-test-only control group design, using 24 male Wistar white rats aged 8-12 weeks and weighing 130-200 grams. The rats were divided into three groups: the positive control (I), green grapefruit extract (II), and normal group (III). The results showed that green grapefruit extract effectively reduced blood glucose levels in experimental animals by a percentage of 98.4%. The Independent T-Test showed a value of ρ>0.05 (0.533), so there was no significant difference in glucose levels between green grapefruit extract and positive control. This study concludes that green grapefruit extract was effective at 98.4% in reducing blood glucose levels in the diabetic rat model, compared to the positive control. The promising results of this study need to be continued by establishing a standardized optimal dose, assessing long-term effects, and implementing clinical trials to evaluate efficacy and safety.